United Arab Emirates : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Arab Emirates. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The 2007 Article IV Consultation on the United Arab Emirates (UAE) examines the near- and medium-term outlook, inflation, and fiscal policy. The rapid expansion is supported by an outward-oriented development strategy and sustained high oil prices. Reforms are under way to strengthen the prudential and regulatory oversight of the banking system and the capital markets; to open the banking sector to greater competition; and to strengthen the legal framework for the financial sector. Executive Directors agreed that the key challenges will be to ensure sustained noninflationary growth and further diversification of the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet